Rancang Bangun Alat Sentrifugal Semi-otomatis Kapasitas 1 kg - Rochaman, Nur; Sakti, Arya Mahendra; Wulandari, Diah; Riandadari, Dyah (Jurnal Rekayasa Mesin, 2025)
This research aims to design and assemble a semi-automatic centrifuge with a capacity of 1 kg that functions to separate liquid and particles in soy milk by utilizing centrifugal force. The need for this tool arises because commercial centrifuges are expensive, have limited capacity, and are less suitable for learning activities in educational laboratories and small-scale industries. The research method applies a Research and Development (R&D) approach that includes literature review, component design, assembly, functional testing, and evaluation of results. This tool is made using a 0.5 HP AC motor equipped with a speed controller via a dimmer and a pulley and V-belt-based transmission system. Tests were carried out at three variations of engine speed (700, 900, and 1100 rpm) and operating duration (15, 20, and 25 minutes) using soy milk samples. The test results show that the tool can run stably and successfully separate liquid from soy milk particles, as indicated by the formation of separate clear and creamy liquid layers. This research provides a contribution in the form of a prototype centrifuge that is economical, has a larger capacity, and is easy to use, so it has the potential to be a practical tool in educational laboratories and technology that is suitable for small-scale industries.